Rapid ingestion and egestion of spherical microplastics by bacteria-feeding nematodes. (December 2020) - Fueser, Hendrik; Mueller, Marie-Theres; Traunspurger, Walter
Abstract: Microplastics, anthropogenically released into freshwaters, settle in sediments, where they are directly ingested by benthic organisms. However, to the best of our knowledge, fine-scale studies of microplastic ingestion and egestion by nematodes, one of the most abundant meiofaunal taxa, are lacking. We therefore conducted a time series of the ingestion and egestion by adult Caenorhabditis elegans and Pristionchus pacificus of 0.5- and 1.0-μm fluorescent polystyrene (PS) beads along with bacteria. The nematodes were exposed to 10 7 beads ml −1 in aqueous medium for 5 min–24 h and pumping rates of C. elegans were determined. In the egestion study, PS bead egestion was monitored in nematodes with high microplastic body burdens for 5 min–24 h in microplastic-free medium. Ingested beads were detected already within 5 min and up to 203 ± 15 PS beads (1.0 μm; C. elegans ) were found after 30 min. Overall, significantly more 1.0-μm than 0.5-μm PS beads were taken up. The distinct feeding behaviors of the two species influenced their PS bead body burdens. Ingested PS beads were almost completely egested within the first 20–40 min in the presence of sufficient food. In C. elegans, 1.0-μm beads were egested less rapidly than 0.5-μm PS beads. Given the rapid ingestion and egestion of the beads, our study demonstrates that the actual amount of ingested and egested microplastics by nematodes in the environment may be several times higher than the microplastic body burdens may imply. However, spherical PS beads did not bioconcentrate in nematodes. Highlights: First fine-scale microplastic ingestion and egestion assay of nematodes. Rapid ingestion of ≤1.0-μm PS beads with first beads in the intestine within 5 min. Distinct nematode feeding behaviors influenced the PS bead body burdens. PS beads were completely egested within 20–40 min in presence of sufficient food. Spherical PS beads had very low bioconcentration factors in nematodes.